2011
DOI: 10.1007/s12016-011-8254-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approaches in Hereditary Angioedema

Abstract: Hereditary angioedema (HAE) is characterized by acute attacks of edema with multiple localizations, the laryngeal angioedema being the most potentially lethal. In HAE, C1-INH impairments cause episodic increase in kallikrein activity leading to attacks of angioedema. Several therapies have recently become available to treat or to prevent HAE attacks, and others are under evaluation for this indication. Plasma-derived C1-INH, bradykinin receptor antagonists (icatibant), kallikrein inhibitors (ecallantide), or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In addition, in humans, severe lung edema can develop in a rare genetic disorder, hereditary angioedema, that results from bradykinin accumulation due to mutations of the C1 esterase/kallikrein inhibitor 39 . Clinical studies have shown that inhibitors of bradykinin can efficiently treat lung edema in these circumstances 40 . Furthermore, the use of ACE inhibitors provides yet another line of clinical evidence for disturbed lung accumulation of bradykinin that can, on rare occasions, lead to severe outcomes 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in humans, severe lung edema can develop in a rare genetic disorder, hereditary angioedema, that results from bradykinin accumulation due to mutations of the C1 esterase/kallikrein inhibitor 39 . Clinical studies have shown that inhibitors of bradykinin can efficiently treat lung edema in these circumstances 40 . Furthermore, the use of ACE inhibitors provides yet another line of clinical evidence for disturbed lung accumulation of bradykinin that can, on rare occasions, lead to severe outcomes 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of C1INH or the presence of a dysfunctional C1INH protein can be found in plasma of patients with HAE. Purified or recombinant forms of C1INH have been, therefore, successfully used for the treatment of HAE [152, 153]. C1INH controls the activation of the classical complement pathway by inactivating the proteinases C1r and C1s, and it also regulates the activation of the lectin pathway potentially by inactivating MASPs 1 and 2 [151, 154, 155].…”
Section: Coagulation and Complementmentioning
confidence: 99%
“…These substances can also be used as prophylaxis. 17 In addition to being an important inhibitor of factor XIIa and kallikrein, C1INH is also the major inhibitor of the proteases C1r and C1s, which belong to the classical complement pathway (Figure 3). Therefore, a deficiency of C1INH or a dysfunctional C1INH protein will lead to uncontrolled activation of the complement and contact system, as well as massive BK release.…”
Section: Hereditary Angioedemamentioning
confidence: 99%